Enerchainability in Agriculture Supply Chain: Examining the adoption of Blockchain and its Energy Efficiency from Farmers’ Perspective - Rajendran, Brintha; Babu, Manivannan; Anandhabalaji, Veeramani (International Review of Management and Marketing, 2025)
This study investigates factors influencing farmers’ acceptance of blockchain technology within the concept of “enerchainability,” which integrates energy efficiency and blockchain to enhance sustainability in the agriculture supply chain (ASC). It examines how farmers’ awareness, social networks, access to technology, and participation in agricultural training shape their behavioral intention to adopt blockchain. Data were collected through a structured survey focusing on demographic factors, social networks, and supply chain challenges. Results show that social networks, technological resources, and education significantly affect blockchain adoption. Younger, educated farmers are more receptive to the technology, while issues like reduced bargaining power and high production costs act as barriers. The study’s findings, though focused on one region, have global relevance for similar agricultural and technological contexts, offering insights into how blockchain can drive sustainability and energy efficiency. The research provides recommendations for policymakers and stakeholders, emphasizing the importance of farmer education and external support for blockchain adoption in ASC.